Parametric studies and design of cushion packaging buffers for drop impact - Mohamed Isa Thameem Ansari. (2008)
In this project, a finite element modeling procedure for performing a virtual product-package drop test is successfully established. The drop test simulation using FEA is done using ANSYS/LS-DYNA. An improved cushion design procedure has been proposed.